Sintonia CTS: um relato Ator-Rede do programa Pesquisa Brasil da Rádio USP FM - Valle, Luciane Ribeiro do (2023)
Versatile since its (official) inauguration, on September 7, 1922, radio began in the country at the hands of scientists belonging to the Brazilian Academy of Sciences, who saw in that medium a rich source of education, culture and scientific dissemination. And it is about scientific dissemination on the radio that this research deals with. It develops from the assumptions of STS studies (Science, Technology and Society), dialoguing and intersecting with Bruno Latour's Actor-Network Theory. A case study of the Pesquisa Brasil program, aired on Rádio USP FM, is carried out. Dating back to 1977, Rádio USP FM is the oldest university radio, on FM frequency, in the country with uninterrupted activity. The path covered here begins with an explanation about the CTS studies, the theoretical choices ending in Bruno Latour, the historical path of scientific dissemination in Brazil, university radio stations, university radio stations in the state of São Paulo, the history of Rádio USP FM and the Pesquisa Brasil program, culminating in a report – in compliance with Latour’s precepts – describing the formation of an ANT (Actor-Network Theory)